2014
DOI: 10.1111/ejh.12338
|View full text |Cite
|
Sign up to set email alerts
|

Early lymphocyte recovery at 28 d post‐transplant is predictive of reduced risk of relapse in patients with acute myeloid leukemia transplanted with peripheral blood stem cell grafts

Abstract: Allogeneic hematopoietic cell transplantation (HCT) is potentially curative for acute myeloid leukemia (AML). Impact of lymphocyte recovery on post-transplant outcomes has been suggested but reports are conflicting. We evaluated the impact of lymphocyte recovery at 28 d post-HCT in 191 AML patients using peripheral blood stem cells as graft. Patients were divided into those with absolute lymphocyte count (ALC) ≥ 0.5 × 10(9) /L (n = 111, 58%; high ALC group) and those with ALC < 0.5 × 10(9) /L (n = 80, 42%; low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
0
27
1
Order By: Relevance
“…Slower recovery likely contributes to the increased incidence of infections and the lack of improvement in OS despite the low incidence of GVHD. One aspect of immune recovery, the ALC, has been shown to be prognostic of outcomes post-HSCT by several investigators [37][38][39][40][41][42]. Although a wide range of ALC values and time points has been reported to predict outcomes of conventional HSCTs, little has been reported for this predictor in older adults and those undergoing TCD HSCTs [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slower recovery likely contributes to the increased incidence of infections and the lack of improvement in OS despite the low incidence of GVHD. One aspect of immune recovery, the ALC, has been shown to be prognostic of outcomes post-HSCT by several investigators [37][38][39][40][41][42]. Although a wide range of ALC values and time points has been reported to predict outcomes of conventional HSCTs, little has been reported for this predictor in older adults and those undergoing TCD HSCTs [42].…”
Section: Discussionmentioning
confidence: 99%
“…The impact on OS and PFS of the day +100 median ALC > 800/μL was likely because of those of the patients with poor-risk disease. In most patients who received DLI [40], it is difficult to determine the impact of DLI on immune recovery because it was often given early in the post-transplant course.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: The recent contribution by Michelis et al (1) convincingly shows that an early recovery of lymphocytes in blood following allogeneic hematopoietic cell transplantation heralds a reduced risk of relapse for patients with acute myeloid leukemia (AML). In a multicenter phase III trial (n = 320), post-consolidation therapy with histamine dihydrochloride and low-dose interleukin-2 (HDC/IL-2) was found to significantly prevent relapse of AML, as accounted for in detail elsewhere (2).…”
Section: Immunotherapy With Histamine Dihydrochloride and Low-dose Inmentioning
confidence: 99%
“…Several researchers, including us, have demonstrated the ALC‐30 could be an available metric for predicting prognosis. However, the conditioning regimen, underlying disease, transplant modalities of most studies are heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that early lymphocyte recovery predicts superior OS after HBMT for myelodysplastic syndrome (MDS) and AML evolving from MDS. However, Michelis et al . revealed that early lymphocyte recovery was related to superior transplant outcomes for AML in HLA‐matched SCT settings.…”
Section: Introductionmentioning
confidence: 99%